PENGARUH TERAPI MUSIK TERHADAP KUALITAS TIDUR PADA LANSIA DENGAN INSOMNIA TAHUN 2021 - Depira Elza Nada; Meynur Rohmah; Zahra Maulidia Septimar (Nusantara Hasana Journal, 2022)
Many elderly experience a decrease in body condition and function, one of which is a decrease in sleep quality, namely insomnia. The results of the survey on insomnia in the elderly according to WHO are quite high, namely 67% (Seoud et al, 2016). The annual incidence of insomnia is about 5% of the elderly. The overall incidence of insomnia is almost the same in men and women but is higher in men 65 years and over, (Foley et al. 2016). This study aims to determine the effect of music therapy on improving sleep quality of elderly with insomnia. This study is a literature review on the effect of music therapy on sleep quality in the elderly with insomnia.. The research found, providing instrumental music therapy for 30 minutes for 4 days on Saturday, Sunday, Monday and Tuesday. Instrumental music given at a slow tempo corresponds to providing instrumental music therapy for 30 minutes. Based on the results of 6 journals that have been reviewed, it is proven that giving music therapy to elderly patients can improve the sleep quality of elderly people who have sleep disorders.